2022
DOI: 10.3389/fdmed.2021.806294
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Transcriptomic Profiling of Human Dental Pulp in Sound and Carious Teeth: A Pilot Study

Abstract: A comprehensive understanding of dental pulp cellular compositions and their molecular responses to infection are crucial for the advancement of regenerative dentistry. Here, we presented a pilot study of single-cell transcriptomic profiles of 6,810 pulpal cells isolated from a sound human maxillary third molar and three carious teeth with enamel and deep dental caries. We observed altered immune cell compositions of the dental pulp in deep, but not enamel ones. Differential expression analysis revealed up-reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 44 publications
2
14
1
Order By: Relevance
“…To complement the mouse tooth sc atlas, we also set out to establish an inclusive sc transcriptomic atlas of healthy human teeth (molars) by combining the at present six publicly available datasets ( Figure 3A ; Table 4 ) ( Krivanek et al, 2020 ; Pagella et al, 2021b ; Shi et al, 2021 ; Yin et al, 2021 ; Hemeryck et al, 2022 ; Opasawatchai et al, 2022 ). Following stringent quality control, 57,906 cells were found suitable for further bioinformatic analysis, with the datasets contributing between 524 and 21,453 cells to the total set, and cells sampled from various dental tissue types (e.g., 24,412 cells from DP and 7,119 from DF) ( Supplementary Figures S3A,B , Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To complement the mouse tooth sc atlas, we also set out to establish an inclusive sc transcriptomic atlas of healthy human teeth (molars) by combining the at present six publicly available datasets ( Figure 3A ; Table 4 ) ( Krivanek et al, 2020 ; Pagella et al, 2021b ; Shi et al, 2021 ; Yin et al, 2021 ; Hemeryck et al, 2022 ; Opasawatchai et al, 2022 ). Following stringent quality control, 57,906 cells were found suitable for further bioinformatic analysis, with the datasets contributing between 524 and 21,453 cells to the total set, and cells sampled from various dental tissue types (e.g., 24,412 cells from DP and 7,119 from DF) ( Supplementary Figures S3A,B , Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…In parallel to composing the healthy tooth atlas, we established a sc transcriptome atlas of diseased human tooth, integrating the at present publicly available datasets from patients with deep caries, enamel caries, chronic apical periodontitis (CAP) and periapical granuloma ( Table 4 ) ( Lin et al, 2022 ; Opasawatchai et al, 2022 ). Following strict quality control, 17,016 cells were retained of which 3,562 and 13,454 cells were derived from dental pulp and periapical diseases (corresponding to the individual datasets), respectively ( Supplementary Figures S3F,G , Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…FASTQ files of single-cell RNA sequencing (scRNA-seq) data were retrieved from published studies (2,(9)(10)(11)(12)(13). The data were selected based on healthy human tissue.…”
Section: Dataset Selectionmentioning
confidence: 99%
“…Researchers have used this technology to generate transcriptomes of developing teeth in mice (7,8). Recent studies of human DP have identified cells involved in tissue development (2), delineated major cellular components of adult DP (9), and described enriched cell types under carious lesion conditions (10).…”
Section: Introductionmentioning
confidence: 99%